Determination of Water Quality Degradation Due to Industrial and Household Wastewater in the Galing River in Kuantan, Malaysia Using Ion Chromatograph and Water Quality Data - Kozaki, Daisuke; Harun, Norhasmira; Rahim, Mohd; Mori, Masanobu; Nakatani, Nobutake; Tanaka, Kazuhiko (Environments (Basel, Switzerland), 2017)
Water quality of the Galing River in Kuantan, Malaysia was examined to understand the anthropogenic environmental load in each administrative section, using water quality monitoring data and land use pattern. The National Physical Plan 2005 identified Kuantan as one of the country’s future growth centers, which has resulted in rapid development and environmental degradation in the past decade. Multiple water quality indexes used by the Department of Environment, Malaysia and concentrations of several ionic species were examined to assess the river’s water quality. The following inferences were drawn in this study: (1) Cl− and Na+ concentrations indicated that the basin area near the eastern urbanized area was subject to lesser human influence and lower environmental burden; (2) the Western side of the Galing River was subject to higher anthropogenic influence and indicated lower class levels of ammoniacal nitrogen, chemical oxygen demand, and dissolved oxygen, compared to the eastern side; (3) Class V or near class V pH values were obtained upstream at the western side of the Galing River in the industrial area; (4) Two types of environmental burden were identified in the western side of the Galing River, namely, inflow of industrial wastewater upstream on the western side and the effect of household wastewater or untreated raw sewage wastewater.